الحماية الدستورية من المؤثرات العقلية - M. Dr.. Iman Jassam Muhammad (AL-Yarmouk Journal, 2026)
The spread of psychotropic substances constitutes a serious challenge to the state, as it is a phenomenon that has taken on various economic, health, security and moral dimensions. It is not related to one country in particular, but rather includes all countries. Therefore, countries alone cannot confront and combat this dangerous phenomenon and limit its spread, and international legal mechanisms have the effective role that they have derived from. Most countries have legislated to confront the crime of drugs and psychotropic substances in accordance with regulatory, preventive and therapeutic means to dry up their sources and punish their perpetrators, abusers and traffickers with the harshest penalties. In agreement with this, the crime of drug abuse is no longer an individual problem, but has become an international crime that crosses national borders, which requires the international community to establish legal rules in National, regional and international scope and intensifying international cooperation in all fields to combat it and stop its spread through all legal means